The factors that affect halal certification among small and medium enterprise food entrepreneurs in Ngawi - Luthfiya, Lulu'; Damayanti, Amilia Yuni; Pibriyanti, Kartika; Marfu'ah, Nurul; Mufidah, Indahtul; Amala, Nur; Hafifah, Cut Ajma Fitira; Fauziatunnisa, Elok (Universitas Ahmad Dahlan, 2024)
A halal lifestyle using halal-certified products is a vital necessity for Muslims. It allows Indonesia to become the world's largest producer and servicer of halal products. However, many uncertified halal products are circulating in the community, and the number of certified halal items tends to be small. Several factors influence the low quality of halal certification products. This Research aimed to identify factors influencing halal certification: education, knowledge, attitudes, behavior, and awareness. The Type of research was crossectional research. The research was conducted in the Ngawi district by comparing entrepreneurs with halal certification and entrepreneurs who still need to have halal certification, with the number of each sample of 26 entrepreneurs. The technique of sampling was purposive sampling. These research variables are factors associated with halal certification, including the level of education, knowledge, attitudes, behavior, and awareness of the entrepreneur acquired through interviews using validated questionnaires and the reliability of the questionnaire. The education, knowledge, and attitude data were analyzed using a chi-square test. The behavior and halal awareness were analyzed using the Fisher test. The statistical test results showed a p-value of < 0.001 on the variables of knowledge, education, attitude, and behavior, so it can be said that knowledge, education, behavior, and attitude positively affect halal certification. However, based on the statistical test on the halal awareness variable, the relationship test results of p-value > 0.05, so it can be said that halal awareness does not positively affect halal certification. This research concludes that education, knowledge, attitudes, and behavior influence legal certification. Awareness of halal behavior does not affect halal certification. Keywords: Attitude, Behavior, Education, Halal awareness, Halal certification knowledge